The Effectiveness of Gallery Walk and Numbered-Heads Together in Teaching Reading Comprehension - Imaduddin Abil Fida; Dwi Anggani Linggar Bharati; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
This study aimed to investigate the effectiveness of gallery walk and numbered-heads together for teaching reading comprehension to students with distinct personalities. The objectives of the study were, to investigate extrovert, and introvert students' scores of reading comprehension to analyze the effectiveness of gallery walk, to investigate extrovert and introvert students' score of reading to analyze the effectiveness of numbered-heads together, to explore the significant differences between extroverted students after learning to use gallery walk and numbered-heads together to teach reading comprehension, to explore the significant differences between introverted students after learning to use gallery walk and numbered-heads together to teach reading comprehension, to analyze how teaching, the personality of students and the reading style interact. This was an experimental study with a 2x2 factorial design. Observations, questionnaires, and tests were used to get the research data. Data from reading tests and questionnaires were analyzed quantitatively using a T-test and ANOVA. The results show that the mean score of the extroverts is 78.40 and introverts is 78.60 after taught using gallery walk technique. While the mean score of the extroverts is 82.70 and introverts is 81.10 after learning using numbered-heads together. These techniques were effective to teach reading. The students’ score of reading comprehension after taught using numbered-heads together technique was higher than those taught by gallery walk. Besides, there was no significant interaction between the use of techniques, student personality, and student reading comprehension.